Review of the implementation of public policy sport at the national level in Colombia and district 2015 (2016)
The rise of Sport in recent years has generated a positive balance in Colombia due to the achievements of high performance athletes at the Olympic Games, promoting physical activity and the use of leisure time not only in educational institutions but also implemented in most of the national population, hence the importance of determining the effects and impact of the implementation of public policy Sport at both national and district level by which prioritize its strategic objectives in the development and promotion of sport , strengthening of institutional organization and sports leadership positioning and also based on the government plan as the allocation of resources for the sports industry is considered public expenditure as established by the Constitution of Colombia.